Calcium Channel TRPV6 Expression in Human Duodenum: Different Relationships to the Vitamin D System and Aging in Men and Women - Walters, Julian RF; Balesaria, Sara; Chavele, Konstantia‐Maria; Taylor, Vivienne; Berry, Jacqueline L; Khair, Umma; Barley, Natalie F; van Heel, David A; Field, Jennifer; Hayat, Jamal O; Bhattacharjee, Abhik; Jeffery, Rosemary; et al. (Journal of bone and mineral research, 2006)
Intestinal absorption of calcium affects bone mineralization and varies greatly. In human duodenum, expression of the calcium channel TRPV6 was directly related to blood 1,25‐dihydroxyvitamin D in men, but effects of age with lower median vitamin D receptor levels were more significant in women. Introduction: The TRPV6 calcium channel/transporter is implicated in animal studies of intestinal calcium absorption, but in humans, its role and relationship to differences in mineral metabolism is unclear. We aimed to characterize TRPV6 expression in human intestine including defining relationships to the vitamin D endocrine system. Materials and Methods: TRPV6 transcript expression was determined in endoscopic mucosal biopsies obtained from normal duodenum. Expression was compared with that in ileum and with in situ hybridization in archival tissues and related to sequence variants in genomic DNA. TRPV6 expression was related in 33 subjects to other transcripts involved in calcium absorption including the vitamin D receptor (VDR) and to blood vitamin D metabolites including 1,25‐dihydroxyvitamin D [1,25(OH)2D]. Results: TRPV6 transcripts were readily detected in duodenum but not in ileum. Expression was highest in villous epithelial cells. Sequence variants in the coding and upstream regions of the gene did not affect TRPV6 expression. The relationship between duodenal TRPV6 expression and 1,25(OH)2D differed in men and women. In men, linear regression showed a strong association with 1,25(OH)2D (r = 0.87, p < 0.01), which was unaffected by age. In women, there was no significant overall relationship with 1,25(OH)2D, but there was a significant decrease with age (r = −0.69, p < 0.001). Individual expression of TRPV6 and VDR was significantly correlated. The group of older women (>50) had lower median levels of both TRPV6 and VDR transcripts than younger women (p < 0.001 and 0.02, respectively). Conclusions: Duodenal TRPV6 expression is vitamin D dependent in men, but not in older women, where expression of TRPV6 and VDR are both reduced. These findings can explain, at least in part, the lower fractional calcium absorption seen in older postmenopausal women.